Votar en tiempos de desinformación: nuevos patrones informativos y comportamiento electoral. - Salazar Rebolledo, Grisel (El Colegio de México, 2024)
In 2024, Mexico faces a challenging electoral process marked by the spread of unverified information, distrust towards critical journalism, and new forms of communication between political actors and voters. Do these challenges represent novel phenomena, or are they modernized forms of political propaganda? This analysis is based on research on the impact of the digital environment in previous elections, both in Mexico and worldwide. Four areas emerge as possible influencing factors: 1) the weakening of journalism, 2) the distrust in traditional media, 3) the transformation in political communication, and 4) the increase in disinformation. The crucial question is whether these elements will radically alter the electoral process or if they are part of a natural political evolution.